Oral care after stroke: Where are we now?. (December 2018) - Lyons, Mary; Smith, Craig; Boaden, Elizabeth; Brady, Marian C; Brocklehurst, Paul; Dickinson, Hazel; Hamdy, Shaheen; Higham, Susan; Langhorne, Peter; Lightbody, Catherine; McCracken, Giles; Medina-Lara, Antonieta; et al.
Purpose: There appears to be an association between poor oral hygiene and increased risk of aspiration pneumonia – a leading cause of mortality post-stroke. We aim to synthesise what is known about oral care after stroke, identify knowledge gaps and outline priorities for research that will provide evidence to inform best practice. Methods: A narrative review from a multidisciplinary perspective, drawing on evidence from systematic reviews, literature, expert and lay opinion to scrutinise current practice in oral care after a stroke and seek consensus on research priorities. Findings: Oral care tends to be of poor quality and delegated to the least qualified members of the caring team. Nursing staff often work in a pressured environment where other aspects of clinical care take priority. Guidelines that exist are based on weak evidence and lack detail about how best to provide oral care. Discussion: Oral health after a stroke is important from a social as well as physical health perspective, yet tends to be neglected. Multidisciplinary research is needed to improve understanding of the complexities associated with delivering good oral care for stroke patients. Also to provide the evidence for practice that will improve wellbeing and may reduce risk of aspiration pneumonia and other serious sequelae. Conclusion: Although there is evidence of an association, there is only weak evidence about whether improving oral care reduces risk of pneumonia or mortality after a stroke. Clinically relevant, feasible, cost-effective, evidence-based oral care interventions to improve patient outcomes in stroke care are urgently needed.